(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2004)
Seven enzymatic hydrolysates from skim milk powder were prepared with the aim of producing dietary supplement for phenylketonurics. A protease from Aspergillus oryzae (AO), papain (PA) and pepsin (PE), separately or in association, were used in different enzyme:substract ratios (E:S), at 50 ºC and total reaction time of 5 h. The distribution of peptides according to chain length was used to evaluate the nutritional quality of protein hydrolysates. Initially, the hydrolysates were fractionated by high-performance liquid chromatography in size-exclusion mode (SE-HPLC) and the rapid method of Correct Fraction Area (CFA) was used for quantifying the peptides and amino acids in the chromatographic fractions. The results showed the advantage of isolated action of each enzyme when compaired with the associations studied. Among all tested preparations, the isolated action of AO and PA, and the association of these two enzymes in E:S ratio of 1% and 2%, respectively, produced hydrolysates having similar peptide prolifes, with the highest proportion of di- and tripeptides and the lowest of free amino acids.